2020
DOI: 10.1080/12298093.2020.1811193
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Soil Higher Fungal Communities between Dead and Living Abies koreana in Mt. Halla, the Republic of Korea

Abstract: To improve our understanding of the relationship between soil higher fungi (belonging to Ascomycota and Basidiomycota) and Abies koreana, we surveyed A. koreana soil fungal communities in a forest in Mt. Halla, Jeju Island, Korea by next-generation sequencing (Illumina Miseq). To confirm the soil higher fungal communities, we collected two types of soils from a defined plot: soils with dead (AKDTs) and living A. koreana (AKLTs), respectively. Soil fungi were classified into 2 phyla, 19 classes, 64 orders, 133 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Applying metagenomics to analyze microbial community from various environments was also conducted in Korea [20][21][22][23][24][25][26]. Of which, NGS platform of Roche 454 was applied to identify airborne fungal community in Seoul [21], while Illumina MiSeq platform was performed to compare soil higher fungal communities associated with dead and living Korean fir (Abies koreana) in Jeju island [26]. However, using metagenomics to analyze endophytic fungal communities in forest trees is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…Applying metagenomics to analyze microbial community from various environments was also conducted in Korea [20][21][22][23][24][25][26]. Of which, NGS platform of Roche 454 was applied to identify airborne fungal community in Seoul [21], while Illumina MiSeq platform was performed to compare soil higher fungal communities associated with dead and living Korean fir (Abies koreana) in Jeju island [26]. However, using metagenomics to analyze endophytic fungal communities in forest trees is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…Members of the Massilia genus were shown in a previous study to have a reduced population in suppressive soils of fungal pathogens and to be negatively correlated with important plant-growth-promoting microbes such as Rhizobium, Paenibacillus , and Streptomyces [ 56 ]. Fungal pathogens are known to be important factors affecting the forest trees’ health status and a clear distinction in the composition was previously reported in a comparative study [ 21 ]. A previous study also reported the effect of soil-borne fungi on the overwintering survival of A. koreana seeds.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the rhizosphere microbiome should be considered as a major aspect in studying forest ecosystems and among the factors contributing to the status of trees. A previous recent study has investigated the community structure of higher fungi between dead and living Korean fir trees and indicated the significant differences in the composition [ 21 ]. However, the bacterial rhizosphere composition and links to tree status remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al. [ 34 ] analyzed the diversity of Ascomycota and Basidiomycota in the rhizosphere soil of A. koreana in Mt. Halla.…”
Section: Discussionmentioning
confidence: 99%